Profil Tugas Perkembangan Peserta Didik Bagi Pengembangan Program Bimbingan Dan Konseling - Winardi, Winardi; Maq, Mumu Muzayyin (Jurnal Eksplorasi Bimbingan dan Konseling, 2023)
This research is based on the development of high school students. The objectives of this study are (1) to determine the description of the developmental tasks of class XI students of SMA Negeri 1 Waled and (2) to develop a guidance and counseling program based on the description of the developmental tasks of high school students. This study uses a descriptive qualitative method. While the research sample uses population sampling. Data processing uses Developmental Task Analysis (ATP) software. The results of the study indicate that the developmental tasks of students have not been achieved optimally.